O território da pesca artesanal da Colônia Z4, Barra Velha, SC: o paradoxo entre a tradição e a modernidade - Machado, Cristina Buratto Gross (2013)
This work studies some questions about artisan`s fishermen territory in Z4 Fishermen Colony its foundation and its changes in the lasts 200 years. Located in Barra Velha/SC this Artisan`s fishermen colony was created based on Azoreans migration. They came to Brazil in order to build a whaler structure. With his arrival began the construction of this space, resulting in Barra Velha. The traditions of these people of the Azores are still present in the city through their artisanal fishery, their popular festivities, their habits and culture. Transmitted by oral tradition from father to son for generations, traditional techniques and accumulated know-how over time are the basis of fishing practiced in Z4 Colony. From the 1960s, there was an acceleration of the urbanization process in the municipality because of the opening of its beaches to tourist activities. These modifications occurred mainly around to the central beach, where is located the fishermen colony, that has since went on to lose its territory due to the appreciation of the area and property speculation. In the same period, with the emergence and development of the fishing industry in Brazil, the territory`s marine fishing also became disputed generating conflicts between artisanal fishermen and industries. Even they had being deterritorialized, they have kept their traditions and resisted the pressures of certain local agents and conflicts against industrial fishing. This artisans fishermen his life and economy activities in Z4 Colony are the subject of this master research that want study his culture, his day-bay-day based on there territory changes. In this research we want to answer some others questions: In what ways modern dialogues with traditional practices of the Colony? What is the relationship between tradition and strength of these subjects in their territory? From these goals we decided to approach the daily lives of these individuals through individual memory / collective, and thus define the Oral History and Simple Observation as our research methods. A deeply in this study show us that is having an overlap of space tourist to space traditionally occupied by fishermen. And yet they have resisted because they rely on that territory as a base of support and also for having links with the place. Another factor that has commandeered the fishermen of their traditional territory is the action of the fishing industry, which explores the nature without considering your time and territory fishermen, removing any possibility of reproduction of fishing, and the state support and incentives to growth.